(untitled) (European Journal of Economics, Finance and Business Development, 2024)
Foods from grains and grain-derived ingredients are among the most important energy and nutrient source for humans. Cereals (e.g., wheat, rice, corn) have been the conventional food materials, while interest is growing in utilizing pseudocereals (e.g., buckwheat, quinoa, amaranth), pulses (e.g., dry peas, chickpea, dry beans), oilseeds (soybean, peanut, hempseed), and other grains for the development of various foods and food ingredients. Grain and food processing converts raw grains to functional ingredients and produces palatable and nutritious end-products. Examples of grain-related processes include, but are not limited to, drying, milling, fractionation, hydration, fermentation, extrusion, cooking, baking, frying, steaming, freezing, etc. Various physical and chemical changes and interactions are expected during these processes, which further affect the nutritional, textural, sensory, and many other quality properties of the products.